New models of care: a liaison psychiatry service for medically unexplained symptoms and frequent attenders in primary care. (December 2017) - Bestall, Janine; Siddiqi, Najma; Heywood-Everett, Suzanne; Freeman, Charlotte; Carder, Paul; James, Mick; Kennedy, Brendan; Moulson, Angela; House, Allan
Abstract : Aims and method: This paper describes the process of setting up and the early results from a new liaison psychiatry service in primary care for people identified as frequent general practice attenders with long-term conditions or medically unexplained symptoms. Using a rapid evidence synthesis, we identified existing service models, mechanisms to identify and refer patients, and outcomes for the service. Considering this evidence, with local contingencies we defined options and resources. We agreed a model to set up a service in three diverse general practices. An evaluation explored the feasibility of the service and of collecting data for clinical, service and economic outcomes. Results: High levels of patient and staff satisfaction, and reductions in the utilisation of primary and secondary healthcare, with associated cost savings are reported. Clinical implications: A multidisciplinary liaison psychiatry service integrated in primary care is feasible and may be evaluated using routinely collected data.